Heavy Alcohol Consumption Effects on Blood Pressure and on Kidney Structure Persist After Long-Term Withdrawal - Sandra Leal; Dinis-Oliveira Ricardo Jorge; Barbosa Joana; Silva Susana Maria; Sá Susana Isabel (Karger Publishers, 2017)
Background/Aims: Heavy ethanol consumption is a risk factor for hypertension and prompts organ damage. There is no information regarding the impact of long-term heavy ethanol consumption on kidney structure and function linking to their hypertensive effects nor the repercussions after withdrawal. Methods: Rats were exposed to ethanol for 24 weeks and, afterwards, a group was assigned to withdrawal for 8 weeks. Blood pressure (BP) was measured and serum biochemical parameters were quantified. Glomerular volume density, areal density of glomerular tuft and renal corpuscles were determined. Angiotensin II type 1 receptor (AT1R) protein expression was evaluated. Results: Twenty-four weeks of ethanol consumption causes atrophy of renal corpuscles and glomeruli and reduces the volume of glomeruli. Glomerular changes induced by ethanol consumption were still evident after withdrawal. Renal AT1R levels were increased in ethanol-treated rats and returned to control levels during withdrawal. Ethanol consumption also induced an increase in BP, uric acid and albumin levels. Upon withdrawal, systolic and mean arterial pressures decreased, but were still higher than in controls rats. Conclusion: Ethanol consumption induces changes in glomerular morphology associated with increased BP and AT1R expression. Long-term withdrawal was inefficient to restore the structural integrity of renal corpuscles and in lowering systolic pressure.